Implementasi Feige-Fiat-Shamir Identification Scheme untuk Autentikasi antara Node dan Gateway pada Module Lora - Audi Fauzan Septano; Ari Kusyanti; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The authentication system using the Long Range (LoRa) module with the Wireless Sensor Network (WSN) mechanism still has problems. The problem lies in the security side of sending authentication data. The authentication that is carried out only matches the ID number as the identity of the sensor node that will communicate to the gateway node. This can cause unauthorized parties to easily break into the system. The Fiege-Fiat-Shamir (FFS) Identification Scheme authentication method is one method that implements the Zero-Knowledge Proof (ZKP) mechanism. The ZKP mechanism is an authentication method used to prove verifier, without providing confidential information or providing a way for other people to find out the confidential information. The authentication is done by matching the evidence generated from the key pair using the FFS identification scheme method. This research resulted in the FFS identification scheme authentication system being successfully implemented in the WSN mechanism using the LoRa module. Attacks carried out by using fake nodes to communicate and replay attacks with duplication of authentication data have been successfully overcome using an FFS identification scheme mechanism.The authentication validation level is 100% which is calculated using confusion matrix.